Determinação da frequência de autorressonância por onda estacionária em enrolamentos solenoidais e proposta de um sistema autorresonante de transferência de energia sem fio utilizando bobinas bifilares abertas - Miranda, Caio Marcelo de (2016)
Common in electrical engineering projects, air-core single-layer solenoid coils can present self-resonant frequencies due to stationary waves effects. The comprehension and determination of these frequencies is of primordial interest for the professionals evolved with these components. In this work, a theory that aims to explain these components behavior at standing wave self-resonance is presented, a practical equation that can determine such frequency values is also developed. The impedance behavior in these components is also discussed and demonstrated, where, based in this theory, two new configurations are presented: a coil with both terminals open and a coil with both terminals grounded. Through a didactic approach the coil and a resonant air-pipe are correlated, and it is explained what is registered in terms of impedance and phase on a vector impedance analyzer when a standing wave self-resonant coil is connected on its terminals. An analysis of the wireless energy transfer in magnetically coupled resonant circuits is also presented, being emphasized the relation between efficiency, relative power transfer and reflected impedance in 2 and 4-coils circuits. A wireless power transfer system using open bifilar coils is proposed. The proposed system has the advantages that the open bifilar coil, different from a conventional coil, has a series self-resonance. Thus, the system behaves as a series-inductor capacitor circuit. Also, since the circuit avoids capacitors, it allows a smaller transmitter and receptor units dimensions, besides avoiding eventual damages to capacitors in higher power applications.